Negative active material for lithium secondary battery and lithium secondary battery comprising the same
Patent Information
- Application Number
- CN202210367300.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-22
- Filing Date
- 2022-04-08
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-04-08
AI Technical Summary
然而,当负极活性物质被设计为具有高功率/容量组成时,热稳定性和机械稳定性可能降低,并且锂二次电池的寿命特性和运行可靠性(operation reliability)可能劣化
[0025]例如,即使在高温下的重复充电/放电期间,也可以通过混合第二负极活性物质来获得提高的容量保持率。
Smart Images

Figure CN115241420B_ABST
Abstract
Description
[0001] Cross-reference and priority claims of related applications
[0002] This application claims priority to Korean Patent Application No. 10-2021-0052386, filed with the Korean Intellectual Property Office (KIPO) on April 22, 2021, the entire disclosure of which is incorporated herein by reference. Technical Field
[0003] This invention relates to a negative electrode active material for lithium secondary batteries and a lithium secondary battery comprising the negative electrode active material. More specifically, this invention relates to a negative electrode active material for lithium secondary batteries comprising a graphite-based material and a lithium secondary battery comprising the negative electrode active material. Background Technology
[0004] With the development of information and display technologies, rechargeable and dischargeable secondary batteries have been widely used as power sources for mobile electronic devices such as portable cameras, mobile phones, and laptops. Recently, battery packs incorporating secondary batteries are being developed and applied to power environmentally friendly vehicles, such as hybrid electric vehicles.
[0005] Secondary batteries include, for example, lithium-ion batteries, nickel-cadmium batteries, and nickel-metal hydride batteries. Lithium-ion batteries have attracted much attention due to their high operating voltage and energy density per unit weight, high charging rate, and compact size.
[0006] For example, a lithium secondary battery may include an electrode assembly comprising a positive electrode, a negative electrode, and a separator layer (separator), as well as an electrolyte impregnating the electrode assembly. The lithium secondary battery may further include a housing having, for example, a pouch shape.
[0007] Carbon-based materials are used as the preferred negative electrode active material for lithium-ion secondary batteries, which offer high capacity, high power, and extended lifespan. However, when the negative electrode active material is designed to have a high power / capacity composition, thermal and mechanical stability may decrease, and the lifespan characteristics and operational reliability of the lithium-ion secondary battery may deteriorate.
[0008] For example, Korean Patent Publication No. 10-1764072 discloses a lithium iron phosphate electrode coated with carbon. Summary of the Invention
[0009] According to one aspect of the present invention, a negative electrode active material for lithium secondary batteries is provided, which has improved capacity and operational reliability.
[0010] According to one aspect of the present invention, a lithium secondary battery having a negative electrode formed of a negative electrode active material is provided.
[0011] A negative electrode active material for a lithium secondary battery includes a first negative electrode active material and a second negative electrode active material, each containing a carbon-based active material and having a crystallite size in the range of 50 nm to 60 nm as defined in Equation 1. The XRD orientation ratio of the first negative electrode active material is in the range of 0.9 to 1.2, and the XRD orientation ratio of the second negative electrode active material is in the range of 1 to 5. The XRD orientation ratio is defined as I(004) / I(110), which is the ratio of the peak intensity of the (004) plane to the peak intensity of the (110) plane.
[0012] [Equation 1]
[0013]
[0014] In Equation 1, L is the crystallite size, λ is the X-ray wavelength (nm) used in the XRD analysis, β is the full width at half maximum (FWHM) of the (110) plane (radians (rad)), and θ is the diffraction angle (radians).
[0015] In some implementations, the first negative electrode active material may include natural graphite, and the second negative electrode active material may include artificial graphite.
[0016] In some implementations, the first negative electrode active material may include natural graphite with a sphericity of 0.9 or higher.
[0017] In some implementations, the XRD orientation ratio of the second negative electrode active material can be greater than that of the first negative electrode active material.
[0018] In some implementations, the XRD orientation ratio of the first negative electrode active material can be in the range of 0.99 to 1.2.
[0019] In some implementations, the XRD orientation ratio of the second negative electrode active material can be in the range of 2 to 4.
[0020] In some implementations, the weight of the second negative electrode active material in the negative electrode active material may be equal to or greater than the weight of the first negative electrode active material.
[0021] In some implementations, the weight ratio of the first negative electrode active material to the second negative electrode active material can be in the range of 50:50 to 5:95.
[0022] A lithium secondary battery includes a negative electrode containing a negative electrode active material for a lithium secondary battery according to the embodiment described above, and a positive electrode opposite to the negative electrode.
[0023] In some embodiments, the positive electrode may include a lithium-transition metal oxide containing nickel (Ni), cobalt (Co), and manganese (Mn) as the positive electrode active material. The molar ratio of Ni in Ni, Co, and Mn in the lithium-transition metal oxide may be 0.6 or higher.
[0024] The negative electrode active material for a lithium secondary battery according to an exemplary embodiment may include a first negative electrode active material and a second negative electrode active material, the first and second negative electrode active materials having crystallite sizes within a predetermined range and different XRD orientation properties. A negative electrode active material using a combination of the first and second negative electrode active materials can achieve high capacity and lifetime stability.
[0025] For example, even during repeated charge / discharge cycles at high temperatures, improved capacity retention can be achieved by mixing a second negative electrode active material. Attached Figure Description
[0026] Figure 1 and Figure 2 The figures show a schematic top plan view and a cross-sectional view of a lithium secondary battery according to an exemplary embodiment. Detailed Implementation
[0027] According to an exemplary embodiment of the present invention, the negative electrode active material for a lithium secondary battery comprises different types of carbon-based materials, and provides improved capacity and lifetime characteristics. According to an exemplary embodiment of the present invention, a lithium secondary battery comprising a negative electrode formed of a negative electrode active material is also provided.
[0028] The invention will be described in detail below with reference to exemplary embodiments and the accompanying drawings. However, those skilled in the art will understand that these embodiments described with reference to the drawings are provided to further understand the spirit of the invention and are not intended to limit the subject matter to be protected as disclosed in the detailed description and the appended claims.
[0029] <Negative electrode active material for lithium secondary batteries>
[0030] The negative electrode active material (hereinafter referred to as negative electrode active material) for lithium secondary batteries according to embodiments of the present invention may include different types of carbon-based active materials.
[0031] In exemplary embodiments, the negative electrode active material may include a graphite-based material. In some embodiments, the negative electrode active material may include a blend or mixture of natural graphite and artificial graphite.
[0032] In an exemplary embodiment, the crystallite size of the negative electrode active material can be 50 nm to 60 nm.
[0033] In an exemplary embodiment, the "crystallite size" can be a value obtained by X-ray diffraction (XRD) analysis of the negative electrode active material in powder form. The crystallite size can be calculated using the full width at half maximum (FWHM) obtained by XRD analysis via Equation 1 below.
[0034] [Equation 1]
[0035]
[0036] In Equation 1 above, L is the crystallite size (nm), λ is the X-ray wavelength (nm), β is the full width at half maximum (FWHM) of the corresponding peak (radians), and θ is the diffraction angle (radians). In an exemplary embodiment, the FWHM in XRD analysis for crystallite size measurement can be obtained from the peak of the (110) plane.
[0037] For example, if the crystallite size of the negative electrode active material exceeds 60 nm, the capacity retention and lifetime performance of the negative electrode active material may deteriorate. If the crystallite size of the negative electrode active material is less than 50 nm, the power and capacity derived from the negative electrode active material may be excessively reduced.
[0038] In some embodiments, the negative electrode active material includes a first negative electrode active material and a second negative electrode active material, and both the first negative electrode active material and the second negative electrode active material can have a crystallite size in the range of 50 nm to 60 nm.
[0039] The first and second negative electrode active materials can have different XRD orientation ratios (or orientation indices).
[0040] The term “XRD orientation ratio or XRD orientation index” used in this paper can be defined as the ratio of I(004) to I(110) by XRD analysis (I(004) / I(110)).
[0041] I(110) and I(004) are the peak intensities or maximum heights of the (110) and (004) planes obtained by XRD analysis of the first and second negative electrode active materials in powder form, respectively.
[0042] In an exemplary embodiment, the XRD orientation index of the first negative electrode active material can be from 0.9 to 1.2, and the XRD orientation index of the second negative electrode active material can be from 1 to 5.
[0043] XRD orientation index can indicate the crystallinity of negative electrode active materials. For example, when the XRD orientation index is too large, the exposure of the active surface of the negative electrode active material may become greater, thereby degrading the life characteristics of the negative electrode or lithium secondary battery. If the XRD orientation index is too small, the crystallinity may decrease, and therefore the capacity of the negative electrode active material may also decrease.
[0044] In an exemplary embodiment, a mixture of a first negative electrode active material and a second negative electrode active material with different XRD orientation indices can be used, thereby improving capacity retention and lifetime characteristics while achieving or maintaining the high capacity characteristics of the secondary battery.
[0045] In some embodiments, the first negative electrode active material may include natural graphite. Compared to synthetic graphite, natural graphite can have improved power / capacity characteristics. Therefore, for example, each of the positive and negative electrodes of a lithium secondary battery, when combined with a high-nickel (high-Ni) positive electrode composition, can achieve high capacity characteristics, as described below.
[0046] Natural graphite may have lower chemical stability and mechanical stability or durability than synthetic graphite. For example, natural graphite may shrink / expand during repeated charge / discharge cycles, potentially causing damage to its granular or crystalline structure.
[0047] As mentioned above, natural graphite with a relatively small XRD orientation index can be used as the first anode active material. Therefore, the high capacity characteristics of the anode can be enhanced by utilizing natural graphite while compensating for the instability of the crystal structure.
[0048] In some implementations, natural graphite particles can be sphere-treated. For example, this can be achieved by impact blending or grinding plate-like graphite. Subsequently, the pulverized graphite powder can be acid-treated with HF, HCl, HNO3, etc., followed by washing. The acid-treated and washed fine particles can then be converted into spherical particles using a pressing process.
[0049] For example, the XRD orientation index of the first negative electrode active material can be changed according to conditions such as temperature and pressure during acid treatment.
[0050] For example, the sphericity of natural graphite particles can be 0.9 or higher, preferably 0.94 or higher, and more preferably 0.96 or higher.
[0051] In some implementations, the second negative electrode active material may include synthetic graphite. Compared to natural graphite, synthetic graphite has relatively improved lifetime characteristics, but it may not be sufficient to provide high capacity characteristics compared to natural graphite.
[0052] As described above, artificial graphite with a relatively large XRD orientation index can be used as the second negative electrode active material. Therefore, by utilizing artificial graphite, the capacity stability and lifetime characteristics at high temperatures can be improved, and the effect of combining artificial graphite with the aforementioned natural graphite can be enhanced.
[0053] Preferably, the XRD orientation index of the first negative electrode active material can be from 0.99 to 1.2, more preferably from 0.99 to 1.1. Preferably, the XRD orientation index of the second negative electrode active material can be from 2 to 4, more preferably from 2.5 to 4.
[0054] The second negative electrode active material may include heat-treated artificial graphite. For example, it can be prepared by pulverizing a carbon-based material with an average particle size (D50) of 5 μm to 10 μm. Preferably, the powder can be heat-treated at a temperature above 3000°C to prepare the second negative electrode active material including artificial graphite.
[0055] Carbon-based materials can include coal-based heavy oil, petroleum-based heavy oil, tar, pitch, coke, etc.
[0056] In one embodiment, the second negative electrode active material may have a secondary particulate structure. For example, artificial graphite in primary particulate form prepared as described above can be mixed with a binder and then heat-treated again to obtain a second negative electrode active material with a secondary particulate structure.
[0057] For example, the XRD orientation index of the second negative electrode active material can be changed according to the temperature and time of the heat treatment used to manufacture artificial graphite.
[0058] According to the above exemplary embodiments, a first negative electrode active material and a second negative electrode active material with different XRD orientation indices can be used together. Therefore, while maintaining / enhancing the advantages of each negative electrode active material and compensating for / suppressing its unfavorable properties, sufficient capacity and lifetime characteristics can be achieved.
[0059] For example, the weight ratio of the first negative electrode active material to the second negative electrode active material (weight of the first negative electrode active material: weight of the second negative electrode active material) can be adjusted within the range of 5:95 to 95:5.
[0060] In a preferred embodiment, the weight of the second negative electrode active material can be greater than or equal to the weight of the first negative electrode active material to obtain high-temperature storage performance and capacity retention performance. In one embodiment, the weight ratio of the first negative electrode active material to the second negative electrode active material (weight of the first negative electrode active material: weight of the second negative electrode active material) can be adjusted in the range of 50:50 to 5:95.
[0061] Preferably, the weight of the second negative electrode active material can be greater than the weight of the first negative electrode active material, and the weight ratio of the first negative electrode active material to the second negative electrode active material (weight of the first negative electrode active material: weight of the second negative electrode active material) can be adjusted within the range of 40:50 to 5:95.
[0062] Furthermore, the crystallite size of the negative electrode active material can be maintained in the range of 50nm to 60nm, thereby more effectively achieving a balance between high power / capacity and lifetime performance.
[0063] <Lithium secondary batteries>
[0064] Figure 1 and Figure 2 The figures show a schematic top plan view and a cross-sectional view of a lithium secondary battery according to an exemplary embodiment.
[0065] Reference Figure 1 and Figure 2 The lithium secondary battery may include an electrode assembly comprising a positive electrode 100, a negative electrode 130, and an insulating layer 140 between the positive and negative electrodes. The electrode assembly may be housed together with an electrolyte impregnating the electrode assembly in a housing 160.
[0066] The positive electrode 100 may include a positive electrode active material layer 110 formed by coating a positive electrode active material onto the positive electrode current collector 105. The positive electrode active material may include a compound capable of reversibly inserting and deintercalating lithium ions.
[0067] In an exemplary embodiment, the positive electrode active material may include a lithium transition metal oxide. For example, the lithium transition metal oxide may include nickel (Ni), and may further include at least one of cobalt (Co) and manganese (Mn).
[0068] For example, lithium transition metal oxides can be represented by the following chemical formula 1.
[0069] [Chemical Formula 1]
[0070] Li 1+a Ni 1-(x+y) Co x M y O2
[0071] In chemical formula 1, -0.05≤α≤0.15, 0.01≤x≤0.3, 0.01≤y≤0.3, and M includes at least one element selected from Mn, Mg, Sr, Ba, B, Al, Si, Ti, Zr, and W.
[0072] In one embodiment, the molar ratio of Ni in the transition metal (e.g., Ni, Co, and Mn) contained in the lithium-transition metal oxide can be 0.5 or more, preferably 0.6 or more, and more preferably 0.8 or more.
[0073] In this context, a high-capacity / power performance can be achieved more effectively through a high-content nickel-cathode composition. As mentioned above, a secondary battery that can stably provide high capacity even during repeated charge / discharge operations can be achieved by combining it with a negative electrode active material that can provide improved extended lifespan characteristics.
[0074] A slurry can be prepared by mixing and stirring the positive electrode active material with a binder, conductive material, and / or dispersant in a solvent. The slurry can be coated onto the positive electrode current collector 105, dried, and pressed to form the positive electrode 100.
[0075] The positive current collector 105 may include, for example, stainless steel, nickel, aluminum, titanium, copper or alloys thereof, preferably aluminum or aluminum alloys.
[0076] The adhesive may include organic-based adhesives such as polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethyl methacrylate, etc., or water-based adhesives such as styrene-butadiene rubber (SBR). The adhesive may be used with thickeners such as carboxymethyl cellulose (CMC).
[0077] For example, PVDF-based binders can be used as positive electrode binders. In this case, the amount of binder used to form the positive electrode active material layer can be reduced, and the amount of positive electrode active material can be relatively increased. Therefore, the capacity and power of lithium secondary batteries can be further improved.
[0078] Conductive materials can be added to facilitate electron migration between active material particles. For example, conductive materials may include carbon-based materials such as graphite, carbon black, graphene, carbon nanotubes, etc., and / or metal-based materials such as tin, tin oxide, titanium oxide, perovskite materials such as LaSrCoO3 or LaSrMnO3, etc.
[0079] The negative electrode 130 may include a negative electrode active material layer 120 formed by coating a slurry containing a negative electrode active material onto the negative electrode current collector 125.
[0080] As described above, the negative electrode active material may include a mixture or blend of a first negative electrode active material and a second negative electrode active material having the above-mentioned crystallite size and XRD orientation index.
[0081] For example, a slurry can be prepared by mixing and stirring a solvent, binder, conductive material, dispersant, etc., with the negative electrode active material according to the exemplary embodiment described above. The slurry can be coated onto the negative electrode current collector 125, dried, and pressed to form the negative electrode 130.
[0082] Alternatively, materials substantially the same as or similar to those used in the positive electrode active material layer 110 may be used. In some embodiments, the adhesive used to form the negative electrode 130 may include, for example, an aqueous adhesive, such as styrene-butadiene rubber (SBR), to be compatible with the carbon-based active material, and carboxymethyl cellulose (CMC) may be used as a thickener.
[0083] The membrane layer 140 may be located between the positive electrode 100 and the negative electrode 130. The membrane layer 140 may include a porous polymer membrane made of, for example, polyolefin-based polymers such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, ethylene / methacrylate copolymer, etc. The membrane layer 140 may also include a nonwoven fabric formed of high-melting-point glass fiber, polyethylene terephthalate fiber, etc.
[0084] In some embodiments, the area and / or volume of the negative electrode 130 (e.g., the contact area with the separator layer 140) can be larger than the area and / or volume of the positive electrode 100. Therefore, lithium ions generated from the positive electrode 100 can be easily transferred to the negative electrode 130 without loss due to, for example, precipitation or sedimentation.
[0085] In an exemplary embodiment, an electrode unit may be defined by a positive electrode 100, a negative electrode 130, and a separator layer 140, and multiple electrode units may be stacked to form an electrode assembly 150 that may have, for example, a jelly roll shape. For example, the electrode assembly 150 may be formed by winding, laminating, or folding the separator layer 140.
[0086] The electrode assembly may be housed together with the electrolyte within the housing 160 to define the lithium secondary battery. In an exemplary embodiment, a non-aqueous electrolyte may be used as the electrolyte.
[0087] For example, non-aqueous electrolytes may include lithium salts and organic solvents. Lithium salts can be derived from Li... + X - Indicates the lithium salt anion X. - It can include, for example, F - C1 - ,Br - I - NO3 - N(CN)2 - BF4 - ClO4 - PF6 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - CF3SO3 - CF3CF2SO3 - (CF3SO2)2N - (FSO2)2N - CF3CF2(CF3)2CO - (CF3SO2)2CH - (SF5)3C - (CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - (CF3CF2SO2)2N - wait.
[0088] Organic solvents may include, for example, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, γ-butyrolactone, propylene sulfite, tetrahydrofuran, etc. These solvents may be used alone or in combination.
[0089] like Figure 1 As shown, the tabs (positive tab and negative tab) can be formed by each of the positive current collector 105 and the negative current collector 125 to extend to one end of the housing 160. The tabs can be welded to one end of the housing 160 to form electrode leads (positive lead 107 and negative lead 127) exposed outside the housing 160.
[0090] Figure 1 The diagram shows the positive electrode lead 107 and the negative electrode lead 127 protruding from the upper side of the housing 160 in a top view, but the position of the electrode leads is not limited to this. Figure 1 The positions shown are as indicated. For example, the electrode leads may protrude from at least one of the two sides of the housing 160, or from the underside of the housing 160. Alternatively, the positive lead 107 and the negative lead 127 may be configured to protrude from different sides of the housing 160.
[0091] Lithium-ion batteries can be manufactured in various shapes, including cylindrical (canned), triangular (prismatic), pouch, and coin-shaped.
[0092] Preferred embodiments are presented below to describe the invention in more detail. However, the following examples are provided merely to illustrate the invention, and those skilled in the art will clearly understand that various changes and modifications can be made within the scope and spirit of the invention. Such changes and modifications are suitably included within the appended claims.
[0093] Examples and Comparative Examples
[0094] 1) Preparation of natural graphite active material (first negative electrode active material)
[0095] Flake graphite was placed in a continuous grinding classifier to obtain spherical natural graphite. The graphite was then acid-treated with sulfuric acid / hydrochloric acid / nitric acid at 80°C for 12 hours, followed by washing and drying to obtain spherical natural graphite with a final purity of 99.8%. The obtained spherical natural graphite had a D50 of 10 μm and an average specific surface area of 10 m². 2 / g.
[0096] Spherical natural graphite and pitch were mixed at a weight ratio of 95:5, coated for 30 minutes using a blade mill, and then fired at 1200°C in a nitrogen atmosphere using an RHK (roller hearth) kiln. Subsequently, the first negative electrode active material was obtained through grading and iron removal processes.
[0097] 2) Preparation of artificial graphite active material (second negative electrode active material)
[0098] Coke was pulverized into powder and then heat-treated at 3000℃ for 20 hours to prepare artificial graphite primary particles with an average particle size (D50) of 7.5 μm.
[0099] Artificial graphite primary particles were mixed with pitch at a weight ratio of 95:5 and heat-treated at 800°C for 10 hours to prepare secondary particles, which were then assembled from the primary particles. The average particle size (D50) of the secondary particles was 16 μm. Subsequently, further heat treatment was carried out at 3000°C to prepare artificial graphite secondary particles.
[0100] The above-mentioned natural graphite particles and artificial graphite particles were used as the negative electrode active material particles in Example 1.
[0101] In the aforementioned manufacturing process, the natural graphite raw material, sphere-treating conditions, heat treatment temperature, and heat treatment time are controlled during the preparation of the first negative electrode active material to prepare natural graphite particles with different XRD orientation indices and crystallite sizes. Furthermore, the type of coke, pulverizing conditions, and heat treatment conditions used to manufacture the second negative electrode active material are controlled to prepare artificial graphite particles with different XRD orientation indices and crystallite sizes.
[0102] XRD analysis was performed on each of the prepared natural graphite particles and artificial graphite particles to measure the XRD orientation index (I(004) / I(110)) and crystallite size according to Equation 1 above.
[0103] The specific XRD analysis equipment / conditions are shown in Table 1 below.
[0104] [Table 1]
[0105]
[0106] As shown in Table 2 below, negative electrode active materials for the Examples and Comparative Examples were prepared, including natural graphite (first negative electrode active material) and / or artificial graphite (second negative electrode active material).
[0107] A negative electrode slurry was prepared comprising 93 wt% negative electrode active material, 5 wt% KS6 as a sheet-like conductive material, 1 wt% styrene-butadiene rubber (SBR) as a binder, and 1 wt% carboxymethyl cellulose (CMC) as a thickener. The negative electrode slurry was coated onto a copper substrate, dried, and pressed to form a negative electrode with an electrode density of 1.6 g / cm³.
[0108] Li[Ni] was mixed as the positive electrode active material in a weight ratio of 96.5:2:1.5. 0.6 Co 0.2 Mn 0.2A slurry was prepared using O2, carbon black as a conductive material, and polyvinylidene fluoride (PVDF) as a binder. This slurry was uniformly coated onto an aluminum foil with a thickness of 12 μm and vacuum dried at 130 °C to prepare a positive electrode for lithium-ion batteries.
[0109] The positive and negative electrodes prepared as described above are each cut to a predetermined size and stacked to form an electrode unit with a separator (polyethylene, thickness: 25 μm) inserted between the positive and negative electrodes. Each tab portion of the positive and negative electrodes is then welded. The welded positive / separator / negative electrode assembly is inserted into a flexible package, and the three sides of the package, except for the electrolyte injection side, are sealed. The tab portions are also included in the sealed portion. Electrolyte is injected through the electrolyte injection side, and then the electrolyte injection side is also sealed. Subsequently, the above structure is impregnated for more than 12 hours.
[0110] An electrolyte was prepared by forming a 1M LiPF6 solution in a mixed solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) / diethyl carbonate (DEC) (25 / 45 / 30; volume ratio), followed by the addition of 1 wt% vinylene carbonate, 0.5 wt% 1,3-propensultone, and 0.5 wt% lithium bis(oxalate)borate (LiBOB).
[0111] Subsequently, the secondary battery prepared as described above was pre-charged for 36 minutes at a current (5A) corresponding to 0.25C. After 1 hour, it was degassed and aged for more than 24 hours, and then formation charging / discharging was performed (charging conditions CC-CV 0.2C 4.2V 0.05C cutoff, discharging conditions CC 0.2C 2.5V cutoff).
[0112] [Table 2]
[0113]
[0114]
[0115] Experimental Example
[0116] 1) DCIR measurement
[0117] The lithium secondary batteries of the examples and comparative examples having the negative electrode compositions shown in Table 2 above were charged / discharged twice (SOC 100%) under conditions of 25°C, 0.5C, and CC-CV. Subsequently, the batteries were recharged under 0.5C CC-CV conditions and discharged at 0.5C until SOC 50%. Afterward, the voltage (first voltage) was measured after a 30-minute rest period.
[0118] Then, after i) discharging at 1C for 10 seconds and then placing for 40 seconds, and ii) charging at 0.75C for 10 seconds and then placing for 40 seconds, the voltage (second voltage) is measured. The DCIR is measured using the difference between the first and second voltages.
[0119] 2) Evaluation of high-temperature storage performance
[0120] At room temperature, the lithium secondary batteries of the embodiments and comparative examples having the negative electrode compositions shown in Table 2 above were charged (CC-CV 1.0C 4.2V 0.05C cutoff) and discharged (CC 1.0C 2.7V cutoff) and set to a SOC 100 state. After being placed in a chamber at 60°C, the charge capacity and discharge capacity were measured every 4 weeks. After being set to the same SOC 100 state again and placed in the chamber, the capacity retention rate compared to the initial discharge capacity was calculated at 4-week intervals.
[0121] 3) Evaluation of 1C / 1C lifetime characteristics
[0122] In a chamber at 45°C, the lithium secondary batteries of the examples and comparative examples having the negative electrode compositions shown in Table 2 above were charged (CC-CV 1.0C 4.2V 0.05C cutoff) and discharged (CC 1.0C 2.7V cutoff) 500 times. The capacity retention rate was calculated as the percentage of the discharge capacity of the 500th cycle relative to the discharge capacity of the first cycle.
[0123] 4) Evaluation of 2C / 1C lifetime characteristics
[0124] In a chamber at 25°C, the lithium secondary batteries of the examples and comparative examples having the negative electrode compositions shown in Table 2 above were charged (CC-CV 2.0C 4.2V 0.05C cutoff) and discharged (CC 1.0C 2.7V cutoff) 500 times. The capacity retention rate was calculated as the percentage of the discharge capacity of the 500th cycle relative to the discharge capacity of the first cycle.
[0125] The evaluation results are shown in Table 3 below.
[0126] [Table 3]
[0127]
[0128] Referring to Table 3, in the embodiments using a mixture of a first negative electrode active material and a second negative electrode active material having the above-mentioned crystallite size range and XRD orientation ratio range, stable DCIR values and lifetime characteristics were provided.
Claims
1. A negative electrode active material for a lithium secondary battery, comprising a first negative electrode active material containing natural graphite and a second negative electrode active material containing artificial graphite, each negative electrode active material comprising a carbon-based active material and having a crystallite size in the range of 50 nm to 60 nm as defined in Equation 1. The XRD orientation ratio of the first negative electrode active material is in the range of 0.9 to 1.2, and the XRD orientation ratio of the second negative electrode active material is in the range of 1 to 5. The XRD orientation ratio of the second negative electrode active material is greater than that of the first negative electrode active material. The XRD orientation ratio is defined as I(004) / I(110), which is the ratio of the peak intensity of the (004) plane to the peak intensity of the (110) plane: [Equation 1] in, In Equation 1, L is the crystallite size, λ is the X-ray wavelength used in the XRD analysis in nm, β is the full width at half maximum (FWHM) of the (110) plane in radians, and θ is the diffraction angle in radians.
2. The negative electrode active material for lithium secondary batteries according to claim 1, wherein the first negative electrode active material comprises natural graphite with a sphericity of 0.9 or higher.
3. The negative electrode active material for a lithium secondary battery according to claim 1, wherein the XRD orientation ratio of the first negative electrode active material is in the range of 0.99 to 1.
2.
4. The negative electrode active material for a lithium secondary battery according to claim 1, wherein the XRD orientation ratio of the second negative electrode active material is in the range of 2 to 4.
5. The negative electrode active material for a lithium secondary battery according to claim 1, wherein the weight of the second negative electrode active material is equal to or greater than the weight of the first negative electrode active material.
6. The negative electrode active material for a lithium secondary battery according to claim 5, wherein the weight ratio of the first negative electrode active material to the second negative electrode active material is in the range of 50:50 to 5:
95.
7. A lithium secondary battery, comprising: A negative electrode comprising the negative electrode active material for lithium secondary batteries according to claim 1; and The positive electrode opposite to the negative electrode.
8. The lithium secondary battery according to claim 7, wherein the positive electrode comprises a lithium-transition metal oxide containing nickel (Ni), cobalt (Co), and manganese (Mn) as the positive electrode active material, and The molar ratio of Ni in Ni, Co, and Mn in the lithium-transition metal oxide is 0.6 or higher.
Citation Information
Patent Citations
Calibrated biasing of sleep transistors in integrated circuits
KR1020210052386A
Carbon material, method for producing same, and use for same
US20180009665A1
Lithium secondary battery
US20180342755A1
Negative electrode active material for secondary battery, and secondary battery
US20200227746A1
Lithium secondary battery and method of manufacturing carbonaceous material for negative electrode of the battery
US5340670A